A Note on Hamiltonian Bypasses in Digraphs with Large Degrees - Darbinyan, Samvel Kh. (Изд-во НАН РА)
Let D be a 2-strongly connected directed graph of order p ≥ 3. Suppose that d(x) ≥ p for every vertex x ∈ V (D) \ {x0}, where x0 is a vertex of D. In this paper, we show that if D is Hamiltonian or d(x0) > 2(p − 1)/5, then D contains a Hamiltonian path, in which the initial vertex dominates the terminal vertex. Դիցուք D -ն 2-ուժեղ կապակցված p-գագաթանի կողմնորոշված գրաֆ է, որի p ¡ 1 գագաթների աստիճանները փոքր չեն p թվից: Եթե D -ն համիլտոնյան է կամ D-ի փոքրագույն աստիճանը մեծ է (p − 1)/5 թվից, ապա այդ գրաֆը պարունակում է համիլտոնյան շրջանցում: Пусть D есть 2-сильно связный p-вершинный орграф, в котором p ¡ 1 вершины имеют степень не меньше чем p. Если D гамильтонов или имеет минимальную степень больше чем (p − 1)/5, то D содержит гамильтонов обход.
Keywords: Mathematical cybernetics; Computer science